Sport, safeguarding and transactional sex: a case study of social networks in Zambian sport. Issue 12 (2nd December 2018) - Solstad, Gerd Marie; Rhind, Daniel
Abstract: In this article, we draw attention to the practice of transactional sex as a risk for adolescent women in Zambia and explore how social networks in organized sport might contribute to mitigate such risks. The study is primarily based on interviews and participatory observation with athletes from two women's sports teams. Three sources of vulnerability were associated with transactional sex: (1) poverty, (2) wanting to fit in with peers and (3) lack of social support. We found that organized sport could provide a context where this vulnerability is lessened through social network support. Specifically, the social network in sport was associated with: (1) social and financial support, (2) role models and (3) team cohesion. However, we stress that the underlying causes of transactional sex, such as gendered poverty, need to be addressed through political and social reform. Meanwhile, transactional sex warrants further attention within the safeguarding in sport literature.